Reconstructing Islamic Education through an Interdisciplinary Approach and Digital Innovation in Creating a Superior, Moderate, and Globally Competitive Generation - Ridwan AI; Dwi Noviatul Zahra (JISEI: Journal of Islamic Studies and Educational Innovation, 2026)
This study aims to reconstruct Islamic education through an interdisciplinary approach integrated with digital innovation to create a superior, moderate, and globally competitive generation. The background of this research lies in the gap between traditional Islamic education, which tends to be normative and text-centered, and the contemporary demands of a rapidly evolving digital and globalized world. By employing a qualitative library research method, this study analyzes various theoretical frameworks from Islamic studies, education, technology, and social sciences. The findings indicate that an interdisciplinary approach enables Islamic education to be more contextual, adaptive, and responsive to modern challenges, while digital innovation enhances accessibility, creativity, and effectiveness in the learning process. Furthermore, the integration of values of moderation (wasatiyyah) within a digitally supported learning environment fosters critical thinking, tolerance, and global awareness among learners. This reconstruction not only strengthens the epistemological foundation of Islamic education but also equips students with relevant competencies needed in the era of globalization and digital transformation. Therefore, Islamic education must continuously evolve by embracing interdisciplinary collaboration and technological advancement to remain relevant and impactful in shaping future generations.